Migrasi Suku Batak Toba ke Daerah Palas, Kota Pekanbaru 1952-2000 - Purnawarman, Yoel Agung; Najmi, Najmi (Lembaga Yasin AlSys, 2025)
Pekanbaru City, the capital of Riau Province, has long been a major migration hub in Sumatra, attracting diverse ethnic groups since the early years of Indonesia’s independence. This study aims to trace the migration history of the Batak Toba people to the Palas area from the initial phase through the fourth period, and to analyze their socio-cultural adaptation strategies in the new environment. Employing historical research methods encompassing the stages of heuristics, source criticism, interpretation, and historiography, this study explores the dynamics of population mobility and intercultural interaction. The findings indicate that the migration of the Batak Toba to Palas was driven not only by economic factors but also by cultural values such as marserak, the Dalihan Na Tolu customary system, and the ethos of hamoraon, hagabeon, and hasangapon. The HKBP Church played a pivotal role in strengthening solidarity, preserving community identity, and facilitating adaptation to new social, cultural, and economic contexts. This study concludes that Batak Toba migration is a complex historical process with a significant impact on the formation of social networks and community integration in multicultural urban areas such as Pekanbaru. These findings underscore the importance of cultural values and community institutions in fostering successful social integration in urban settings.